KOMUNIKASI PERSUASIF ISO 45001:2018 OLEH KONSULTAN Y KEPADA MANAJEMEN PERUSAHAAN X DI YOGYAKARTA - Masjuli, Masjuli (IDENTIFIKASI, 2020)
ISO 45001: 2018 was published on 12 March 2018 to replace OHSAS 18001: 2007 so that many lecturers, students, workers and management teams of an organization are interested in studying it. One of them was the management team of company X who attended the ISO 45001 training held by consultant Y in Yogyakarta. This study aims to determine whether the persuasive communication provided by the communicator to the communicant is effective or not. The research methodology used is descriptive statistics. The results showed that the management team of company X had understood the messages given by the communicators. It can be concluded that ISO 45001 persuasive communication runs effectively.